Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.foodchem.2019.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and cadmium contents in Brazilian rice from different origins can vary more than two orders of magnitude

Abstract: Please cite this article as: Kato, L.S., de Nadai Fernandes, E.A., Raab, A., Bacchi, M.A., Feldmann, J., Arsenic and cadmium contents in Brazilian rice from different origins can vary more than two orders of magnitude, Food Chemistry (2019), doi: https://doi. AbstractBrazil is a major producer of rice, but there is not enough information about As and Cd in rice grown under different conditions in this country. Here, As and Cd were determined by ICP-MS and species of As by HPLC-ICP-MS in Brazilian husked rice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This is generally attributed to the fact that the southern Chinese provenances tend to be more impacted by the extensive base metal ore exploitation that occurs in these regions. While countries outside China have been less considered, the results presented here equate to those that have been published for rice from Australia, India, Italy, Bangladesh, Thailand, and Japan (Rahman et al, 2014) as well as Brazil (Kato et al 2019) and Italy (Pastorelli et al 2018). All these studies, including the global survey presented here, illustrate that south-eastern Chinese provinces are the highest, so far surveyed, with respect to grain cadmium.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is generally attributed to the fact that the southern Chinese provenances tend to be more impacted by the extensive base metal ore exploitation that occurs in these regions. While countries outside China have been less considered, the results presented here equate to those that have been published for rice from Australia, India, Italy, Bangladesh, Thailand, and Japan (Rahman et al, 2014) as well as Brazil (Kato et al 2019) and Italy (Pastorelli et al 2018). All these studies, including the global survey presented here, illustrate that south-eastern Chinese provinces are the highest, so far surveyed, with respect to grain cadmium.…”
Section: Discussionsupporting
confidence: 65%
“…When it comes to variation in rice cadmium, besides the aforementioned surveys of China (Chen et al 2018;Fang et al 2014;Hu et al 2016;Ke et al 2015;Mu et al 2019;Williams e al. 2007), the rest of the globe is either considered country-by-country (Adomako et al 2011;Joy et al 2017;Kato et al 2019;Pastorelli et al 2018;Rahman et al 2014;Sommella et al 2013; and other surveys compiled in Ke et al 2015) or with a limited inter-country overview (Meharg et al 2013). Here we intend to build from previous surveys (Adomako et al 2011;Meharg et al 2013;Joy et al 2017;Sommella et al 2013;Williams et al 2007) by integrating with these previous studies new cadmium data derived from a rice survey designed to represent the global supply-chain that has been characterised for arsenic speciation (Carey et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, in the condition of e[CO2], several factors can be altered, influencing the As uptakes, such as higher root growth and changes in the composition of the rhizosphere. It is also essential to carry out Researchers have investigated As uptake and concentration in rice grain along two central lines: toxicity in the plant [55,56] and accumulation in grain [26,57]. Studies have demonstrated that high [CO 2 ] reduces the concentration of several micronutrients, including iron, zinc, copper, calcium, and manganese, in rice grains and other species [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic (As) and cadmium (Cd) are more available for plant uptake in anaerobic soils in continuously flooded rice fields [25,26]. Recent studies have raised concerns regarding As and Cd concentrations in rice grain [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenate accumulation in rice 9,[35][36][37][38] , fruit and flowering plants 39-41 is considered a major problem for consumers. It has been suggested that uptake of arsenate in plants relies on PHT phosphate transporters, a specific family of plant plasma membrane proteins [42][43][44] , but the detailed mechanism has not yet been elucidated due to the lack of an appropriate visualization tool.…”
Section: Bioimaging Of Arsenate and Pi In Wolffiamentioning
confidence: 99%